A search for ionized jets towards massive young stellar objects. Issue 1 (1st May 2016) - Purser, S. J. D.; Lumsden, S. L.; Hoare, M. G.; Urquhart, J. S.; Cunningham, N.; Purcell, C. R.; Brooks, K. J.; Garay, G.; Gúzman, A. E.; Voronkov, M. A.
Abstract: Radio continuum observations using the Australia telescope compact array at 5.5, 9.0, 17.0 and 22.8 GHz have detected free–free emission associated with 45 of 49 massive young stellar objects and H ii regions. Of these, 26 sources are classified as ionized jets (12 of which are candidates), 2 as ambiguous jets or disc winds, 1 as a disc-wind, 14 as H ii regions and 2 were unable to be categorized. Classification as ionized jets is based upon morphology, radio flux and spectral index, in conjunction with previous observational results at other wavelengths. Radio luminosity and momentum are found to scale with bolometric luminosity in the same way as low-mass jets, indicating a common mechanism for jet production across all masses. In 13 of the jets, we see associated non-thermal/optically thin lobes resulting from shocks either internal to the jet and/or at working surfaces. 10 jets display non-thermal (synchrotron emission) spectra in their lobes, with an average spectral index of α = −0.55 consistent with Fermi acceleration in shocks. This shows that magnetic fields are present, in agreement with models of jet formation incorporating magnetic fields. Since the production of collimated radio jets is associated with accretion processes, the results presented in this paper support the picture of disc-mediated accretion for the formation of massive stars with an upper limit on the jet phase lasting approximately 6.5 × 10 4 yr. Typical mass-loss rates in the jet are found to be 1.4 × 10 −5 M⊙ yr −1 with associated momentum rates of the order of (1–2) × 10 −2 M⊙ km s −1 yr −1 .